A Novel Design of a Quadruped Robot for Research Purposes. (4th July 2014) - Geva, Yam; Shapiro, Amir
This paper presents the design of a novel quadruped robot. The proposed design is characterized by a simple, modular design, and easy interfacing capabilities. The robot is built mostly from off-the-shelf components. The design includes four 3-DOF legs, the robot body and its electronics. The proposed robot is able to traverse rough terrain while carrying additional payloads. Such payloads can include both sensors and computational hardware. We present the robot design, the control system, and the forward and inverse kinematics of the robot, as well as experiments that are compared with simulation results.